Experiencia de los psicoterapeutas que trabajan con pacientes con trastorno de personalidad límite - Matto Cobeña, Stefania Antonella (2024)
The present study aimed to identify the manifestations of the psychotherapist that arise in the therapeutic relationship, identify the factors that influence the success or failure of therapy from the psychotherapist's perspective, and describe the coping strategies of psychotherapists dealing with BPD intervention that allows for effective intervention and generates significant change. The participants were 11 psychotherapists with 5 or more years of experience working with these patients. Semi-structured interviews were used, and the data were analyzed using content analysis. Four categories were identified: "Therapist's Manifestations," "Factors influencing therapy success or failure," "Therapist's coping strategies," and "The purpose of therapy." It is highlighted that the interaction with the patient can lead to a variety of reactions in the professional, which should be employed as a tool in favor of therapy. However, these reactions can also cause significant distress, so the therapist must take into account certain aspects that can contribute to the success or failure of therapy. Additionally, the therapist's intervention is influenced by a set of elements such as analytical ability, empathy, mindfulness, selfdisclosure and genuineness, self-awareness, and experience. Furthermore, therapists confirm the importance of their perspective of therapy and their role in the patient's change.